2020
DOI: 10.1177/1971400920953299
|View full text |Cite
|
Sign up to set email alerts
|

Delayed rupture of intracranial aneurysms after placement of intra-luminal flow diverter

Abstract: Background Though flow diverter is a safe and efficient modality, some patients can experience delayed aneurysmal rupture. The mechanism of delayed rupture is still obscure to us. Methods We performed a systematic search in the PubMed database for patients with delayed rupture of intracranial aneurysms after flow diverter placement. Results A total of 36 articles reporting on 60 patients were included in the final analysis. Of the 49 patients with description of presenting symptoms, six (12.2%) patients were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 53 publications
0
29
0
2
Order By: Relevance
“…Delayed aneurysmal rupture is another potentially serious complication of FD treatment that can have a devastating outcome. Hou et al ( 34 ) performed a systematic review of patients who experienced delayed rupture after FD placement and concluded that increased intra-aneurysmal pressure, destabilization of the aneurysm wall by intra-aneurysmal thrombus, persistent residual intra-aneurysmal flow, large or giant size, presence of symptoms, and FD-induced mechanical injury might contribute to delayed rupture. In our series, four patients with aneurysm sizes ranging from 22 to 40 mm developed delayed rupture; three occurred from aneurysms located in the proximal segment, including two with a VBJ aneurysm that was treated with a single PED without coiling and contralateral vertebral sacrifice.…”
Section: Discussionmentioning
confidence: 99%
“…Delayed aneurysmal rupture is another potentially serious complication of FD treatment that can have a devastating outcome. Hou et al ( 34 ) performed a systematic review of patients who experienced delayed rupture after FD placement and concluded that increased intra-aneurysmal pressure, destabilization of the aneurysm wall by intra-aneurysmal thrombus, persistent residual intra-aneurysmal flow, large or giant size, presence of symptoms, and FD-induced mechanical injury might contribute to delayed rupture. In our series, four patients with aneurysm sizes ranging from 22 to 40 mm developed delayed rupture; three occurred from aneurysms located in the proximal segment, including two with a VBJ aneurysm that was treated with a single PED without coiling and contralateral vertebral sacrifice.…”
Section: Discussionmentioning
confidence: 99%
“…27 As already mentioned, in cases where an FDD already exists, it can be used as a scaffold for further treatment either using additional FDDs or embolic agents. 16 , 20 , 21 , 28…”
Section: Discussionmentioning
confidence: 99%
“…18,[23][24][25] Investigation of the hemodynamic changes within cerebral aneurysms after FD treatment remains desirable, since associated complications such as delayed aneurysm growth or rupture remain topics in current literature. 15,[26][27][28] This study retrospectively examined the predictive value of various iFlow parameters after flow diverter treatment of cerebral aneurysms. Cattaneo et al previously described promising preclinical evaluation criteria, that are based on a comparison between intraluminal and intra-aneurysmal TDCs, aimed at the difference of maximum contrast agent intensity, delay between intensity peaks and ratio of intensity decrease.…”
Section: Discussionmentioning
confidence: 99%
“…18,2325 Investigation of the hemodynamic changes within cerebral aneurysms after FD treatment remains desirable, since associated complications such as delayed aneurysm growth or rupture remain topics in current literature. 15,2628…”
Section: Discussionmentioning
confidence: 99%